Integration of Morphometric Analysis and Synthetic Unit Hydrograph Methods for Hydrological Assessment in the Warana River Basin, Maharashtra, India - Patil, Suraj Kalgonda; Sajane, Amitkumar Sukumar; Lambe, Jagdish Subhash; Sakhare, Vishal Dattatray; Dixit, Ajinkya Shrikant; Pise, Pranav Anant; Rodrigues, Joyluis Shalwador; Hajare, Amar Vilas (Engineering Research: Perspectives on Recent Advances Vol. 4, 2025)
This study aims to develop and evaluate average representative unit hydrographs (UHs) for the upper Warana River basin, Maharashtra, India, based on isolated storm events. Synthetic Unit Hydrographs (SUHs) were constructed using four established methods: Snyder’s modified method, Soil Conservation Service (SCS) dimensionless hydrograph, Central Water Commission (CWC) method, and Commons' dimensionless hydrograph. The SUHs were assessed for ungauged basins with similar hydrological characteristics, and their correlation coefficients were calibrated and validated. Morphometric analysis of the basin indicated moderate to high flood potential and moderate recharge capacity for the Warana River basin, with Sub-basins 1 and 3 exhibiting similar characteristics, while Sub-basin 2 showed low flood potential and high recharge capacity. Snyder’s method emerged as the most effective approach, yielding a peak discharge percentage error of 0.26% for the Warana River basin and 0.32% for Sub-basin 1. The Snyder coefficients Cp =0.55 and Ct=1.06 were found to be suitable as regional coefficients for basins with analogous hydroclimatic conditions. Comparative analysis revealed that Snyder's SUH closely aligned with observed UHs, demonstrating high reliability for runoff prediction. The successful validation of Snyder’s model underscores its utility in water resources management, enabling accurate flood prediction, water allocation, and reservoir operation. These findings establish Snyder’s SUH as a robust tool for hydrological modelling in ungauged basins with similar hydroclimatic settings.